Singapore's fiscal strategies for growth a journey of self-reliance - Lee, Kok Fatt (World Scientific Pub., 2018)
Singapore's fiscal strategies have helped sustain the country's growth as a small and open economy. This book is a pioneering effort in terms of providing a non-technical, holistic view of Singapore's strategies. Besides providing a documentation of the development of Singapore's fiscal strategies over the years, the current and impending national challenges to be addressed by fiscal strategies are also discussed. The author also addresses the importance of culture to a nation's success, and highlights the impact of fiscal policy in this regard.